Interprofessional collaboration between pharmacists and community health workers: a scoping review - Carole Bandiera; Sabuj Kanti Mistry; Elizabeth Harris; Mark F Harris; Parisa Aslani (International Journal for Equity in Health)
Abstract Introduction Community health workers (CHWs) help bridge the cultural gap between health services and the communities they serve. CHWs work with physicians, nurses and social workers, but little is known about their collaboration with pharmacists. This scoping review aims to describe the interprofessional collaboration between CHWs and pharmacists, the types of interventions they deliver and CHWs’ and pharmacists’ specific roles within these interventions. Method The scientific literature published in PubMed, Embase, MEDLINE, Scopus, Web of Science, PsycInfo, CINAHL and the grey literature were searched. Inclusion criteria were that the research (i) involved pharmacists and CHWs working collaboratively and (ii) included an intervention, service or program. One researcher screened all articles, and two reviewers screened 6% of articles (20/340) assessed for eligibility, using the software Covidence. After the discrepancies were resolved, data from the included articles were extracted using a customized template for data extraction and synthesized narratively. Results Eighteen studies met the inclusion criteria. Most were conducted in the USA (14/18) and were published since 2020 (12/18). Most interventions involved medication reviews, support for medication adherence, disease prevention or addressing the social determinants of health. Pharmacists had primarily clinical roles (i.e., medication reconciliation and patient education), while the CHWs’ roles consisted of collecting patient information, supporting patient self-management, bridging the cultural gap by translating information in the patient’s language and ensuring patient follow-up. The collaborative practice occurred via interprofessional referral, ranging from the CHW facilitating the link between the patient and the pharmacist, and information sharing between the CHW and the pharmacist, to an interprofessional collaborative practice where CHWs and pharmacists delivered the intervention together. Conclusion While CHWs and pharmacists had independent roles as part of the interventions, they also collaborated at various levels to deliver services to patients. CHWs have an important role to play in bridging the cultural gap between the patient and the pharmacist, in improving patient referral so that more patients can benefit from pharmaceutical services, and in identifying patients’ social determinants of health. CHWs and pharmacists can work synergistically and collaboratively to tailor an intervention to the patient’s needs, which can improve and optimize pharmaceutical services, and may ultimately positively impact health outcomes.